Influence of carboxypeptidases on free amino acid, peptide and methylpyrazine contents of under-fermented cocoa beans - Yusep, I.; S., Jinap; B., Jamilah; S., Nazamid (Society of Chemical Industry, 2002)
A study of the action of two carboxypeptidases on free amino acids, peptides and methylpyrazines in under-fermented cocoa beans was carried out. Carboxypeptidase B from porcine pancreas and carboxypeptidase Y from baker's yeast were used separately for digestion. Hydrophobic free amino acids (alanine, valine, isoleucine, leucine, phenylalanine and tyrosine) were predominantly produced in samples digested with both carboxypeptidase B and Y. The peptide patterns of samples digested with both carboxypeptidases were similar to that of the control. The concentration of 2,3,5,6-tetramethylpyrazine in samples with carboxypeptidase B addition was significantly higher than those of 2,5-dimethyl- and 2,3,5-trimethylpyrazine; the concentration of 2,3,5-trimethylpyrazine was highest (1727.86 μg per 100 g) in the sample with carboxypeptidase B addition that had been incubated for 24 h. These findings indicate that carboxypeptidase B from porcine pancreas was more prominent in the formation of cocoa-specific aroma.